Imagining the Future of Europe: Is Transnational Left Populism the Way Forward? - Blokker, Paul; Honová, Petra A.; Moskvina, Yuliya; Šrám, Kristián (PARTECIPAZIONE E CONFLITTO, 2024)
The European Union is facing a ’poly-crisis’. As a result, reflections on the future of Europe have intensified (one example is the Conference on the Future of Europe). In discussing visions of Europe, scholars generally pit cosmopolitanism against communitarianism, or pro-Europeanism against Euro-scepticism. Visions of Europe’s future are however more complex and irreducibly plural. The article examines the ideational landscape of the EU by, first, mapping a plurality of prominent, frequently used discourses on European integration. Second, we examine a tendency towards reproducing the status quo in dealing with the poly-crisis. Despite the rich ideational plurality, dominant forces in the EU tend not to be inclined to significantly reform the EU. The third part of the paper examines one exception, in the form of left transnational populism, which proposes a critical, but constructive, alternative understanding of integration. The analysis of this left populist composite, critical Europeanist discourse, focusses on the most developed, even if marginal, transnational left populist project, DiEM25. The article concludes by indicating both the relevance of the critical Europeanist discourse and the formidable, practical obstacles the project faces